Effects of 6-weeks high-intensity interval training in schoolchildren with insulin resistance: Influence of biological maturation on metabolic, body composition, cardiovascular and performance non-responses (2017)
Background: Previous studies have observed significant heterogeneity in the magnitude of change in measures of metabolic response to exercise training. There are a lack of studies examining the prevalence of non-responders (NRs) in children while considering other potential environmental factors involved such as biological maturation. Aim: To compare the effects and prevalence of NRs to improve the insulin resistance level (by HOMA-IR), as well as to other anthropometric, cardiovascular, and performance co-variables, between early (EM) and normal maturation (NM) in insulin-resistance schoolchildren after 6-weeks of HIIT. Methods: Sedentary children (age 11.4 ± 1.7 years) were randomized to either HIIT-EM group (n = 12) or HIIT-NM group (n = 17). Fasting glucose (FGL), fasting insulin (FINS) and homeostasis model assessment of insulin resistant (HOMA-IR) were assessed as the main outcomes, as well as the body composition [body mass, body mass index (BMI), waist circumference (WC), and tricipital (TSF), suprailiac (SSF) and abdominal skinfold (AbdSF)], cardiovascular systolic (SBP) and diastolic blood pressure (DBP), and muscular performance [one-repetition maximum strength leg-extension (1RMLE) and upper row (1RMUR) tests] co-variables were assessed before and after intervention. Responders or NRs to training were defined as a change in the typical error method from baseline to follow-up for the main outcomes and co-variables. Results: There were no significant differences between groups in the prevalence of NRs based on FGL, FINS, and HOMA-IR. There were significant differences in NRs prevalence to decrease co-variables body mass (HIIT-EM 66.6% vs. HIIT-NM 35.2%) and SBP (HIIT-EM 41.6% vs. HIIT-NM 70.5%). A high risk [based on odds ratios (OR)] of NRs cases was detected for FGL, OR = 3.2 (0.2 to 5.6), and HOMA-IR, OR = 3.2 (0.2 to 6.0). Additionally, both HIIT-EM and HIIT-NM groups showed significant decreases (P < 0.05) in TSF, SSF, and AbdSF skinfold, and similar decreases in fasting insulin and HOMA-IR. The HIIT-EM group showed significant decreases in SBP. The HIIT-NM group showed significant increases in 1RMLE and 1RMUR. A large effect size was observed for pre-post changes in TSF in both groups, as well as in SSF in the HIIT-NM group. Conclusion: Although there were no differences in the prevalence of NRs to metabolic variables between groups of insulin resistance schoolchildren of different maturation starting, other NRs differences were found to body mass and systolic BP, suggesting that anthropometric and cardiovascular parameters can be playing a role in the NRs prevalence after HIIT. These results were displayed with several metabolic, body composition, blood pressure, and performance improvements independent of an early/normal maturation or the prevalence of NRs. © 2017 Alvarez, Ramírez-Campillo, Ramírez-Vélez and Izquierdo.